The Effectiveness Of Marmet Technique And Oxytocin Massage On Breast Milk Production In Postpartum Mothers At Sukarami Community Health Center - Zelharsandy, Vika Tri (Jurnal Kesehatan Abdurrahman, 2025)
Breast milk is the first natural food and drink for babies, which provides all the vitamins, nutrients and minerals needed by babies for growth in the first six months. ASI also contains antibodies from the mother which become their immune system and help fight disease. Non-pharmacological therapy such as acupuncture, infrared radiation, and massage techniques. The most likely therapy carried out by families to increase breast milk production is through massage techniques or marmet techniques. The design of this study is a two-group pretest posttest design. Based on the results of the statistical analysis test, the p value = 0.001 <α value = 0.05 means that there is a difference in the marmet technique and oxytocin massage on increasing breast milk production in postpartum mothers. From the test results above, it can be concluded that there is an effect of the effectiveness of the marmet technique and oxytocin massage on breast milk production in postpartum mothers. Keyword: marmet technique, oxytocin massage, breast milk production, post partum